Advice for a Communicative Learning Environment - Cerise Santoro (Westcliff University, 2017)
Currently the Philippines is the last country in Asia implementing a ten-year education plan providing education until tenth grade before students reach university level. The education change will aid future Filipino professionals to compete globally since it is the recognized standard throughout the world. However, with expanding pressure for EFL teachers to implement new programs and systems it has left a gap between students being proficient academically and communicatively at the same time. The issue continues to increase since inappropriate implementation of activities leave students perceiving the communicative approach as frivolous and unproductive. As a result, students do not appreciate an active learning environment in the classroom.